2014
DOI: 10.1021/ac502378e
|View full text |Cite
|
Sign up to set email alerts
|

Full Antibody Primary Structure and Microvariant Characterization in a Single Injection Using Transient Isotachophoresis and Sheathless Capillary Electrophoresis–Tandem Mass Spectrometry

Abstract: Here we report the complete characterization of the primary structure of a multimeric glycoprotein in a single analysis by capillary electrophoresis (CE) coupled to mass spectrometry (MS). CE was coupled to electrospray ionization tandem MS by means of a sheathless interface. Transient isotachophoresis (t-ITP) was introduced in this work as an electrokinetically based preconcentration technique, allowing injection of up to 25% of the total capillary volume. Characterization was based on an adapted bottom-up pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 35 publications
2
72
0
Order By: Relevance
“…CESI‐MS is capable of analyzing simultaneously very small (<300 Da) and very large peptides (>8000 Da) under the same experimental conditions achieving 100% sequence coverage within one single run and one enzymatic digest. High ionization efficiencies provided by CESI and highly sensitive MS allowed in‐depth analysis of glycosylations with relative abundance varying more than 3 orders of magnitude . As a further evaluation, we have used CESI‐MS/MS to compare trypsin maps of trastuzumab and trastuzumab‐B and cetuximab and cetuximab‐B .…”
Section: Resultsmentioning
confidence: 99%
“…CESI‐MS is capable of analyzing simultaneously very small (<300 Da) and very large peptides (>8000 Da) under the same experimental conditions achieving 100% sequence coverage within one single run and one enzymatic digest. High ionization efficiencies provided by CESI and highly sensitive MS allowed in‐depth analysis of glycosylations with relative abundance varying more than 3 orders of magnitude . As a further evaluation, we have used CESI‐MS/MS to compare trypsin maps of trastuzumab and trastuzumab‐B and cetuximab and cetuximab‐B .…”
Section: Resultsmentioning
confidence: 99%
“…This property may be important, especially in case of more complex glycoproteins or for mAbs having several glycosylation sites. Moreover, it must be mentioned that our CE-ESI-MS methodology is not restricted to the sole purpose of glycopeptides characterization and quantitation, but it can also be employed for the overall characterization of mAbs, including primary structure assessment with complete sequence coverage as well as identification and quantification of a large number of PTMs, all performed within a unique single analysis [27]. In our opinion, this work proves that CE-ESI-MS could be a viable alternative to LC-ESI-MS for glycosylation profiling and should be considered as an innovative approaches in MS-based proteomics applied to mAbs characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant instrumental development to achieve LIF and MS dual detection, their strategies allowed to perform quantitative analysis provided by the on-line LIF trace and to increase confidence by providing accurate mass information [26]. More recently, Gahoual et al reported the development of CE-ESI-MS technique for the characterization of the primary structure of mAbs performed in a single injection [27]. Based on a bottom-up approach, they highlighted the benefits of using electrophoretic separation in complement to chromatographic separation, which is conventionally applied in this type of study.…”
Section: Introductionmentioning
confidence: 99%
“…11 More recently, Gahoual et al characterized 15 glycopeptides using a bottom-up approach by CESI-MS/MS. 13 In our work, we could identify a total of 15 glycans divided between 7 for the Fc/2 N-glycosylation and 8 for the F(ab′) 2 N-glycosylation (Tables S-1 and S-2, Supporting Information). Regarding the Fc/2 domain, branched glycan structures are primarily composed of fucose, Nacetylglucosamine, and mannose but can differ in the number of terminal galactose, mannose, or N-acetylglucosamine residues.…”
Section: Cze/collection Fractionmentioning
confidence: 95%